Role of Trace Elements in Natural Amethysts in Colouring - TUMUKLU, ALI; GUMUS, HANDE; SEN, SEZER (Asian Journal of Chemistry, 2010)
In this study, a research has been conducted on trace elements that are likely to colour natural amethyst, a semiprecious gemstones. The trace elements of two amethyst samples, one in purple and the other one in lilac, which were procured from Dursunbey (Balikesir, Turkey) were defined. Comparing the trace elements obtained with the previous studies, it was concluded that the colour purple intensified as Fe and Mn proportions in amethysts increased and the colour purple turned into a lighter purple, which was lilac as the proportion of Sb element diminished.